Realizing Legal Certainty in Electronic Land Certificates: A Critical Reflection on Ontario’s Legislative Model for Indonesia - Andilsim, Weyni; Tan, Winsherly; Jaya, Febri (SIGn Jurnal Hukum, 2025)
The digital transformation of land administration in Indonesia, under the framework of Government Regulation Number 18 of 2021, marks a crucial step toward modernizing public services. However, a fundamental problem of legal certainty for land rights arises from its delegative model of authority, under which essential technical regulations are issued through the Regulation of Minister of ATR/KBPN Number 3 of 2023. This reliance on a ministerial-level regulation creates potential long-term juridical and operational vulnerabilities. This research aims to critically analyze the weaknesses of this delegative model and project strategic solutions, employing a normative legal research method with a functional comparative approach. The Province of Ontario, Canada, a global pioneer, was selected as the comparative jurisdiction. The analysis reveals that Indonesia’s delegative model is exacerbated by practical challenges, including technological infrastructure gaps, a deficit in public trust, and uneven digital literacy. Conversely, Ontario’s integrative legislative model—supported by a comprehensive ecosystem of regulations at the Act of Parliament level, a mature public-private partnership, and strict access governance—has been functionally proven to achieve superior levels of legal certainty and efficiency. It is concluded that to achieve complete legal certainty, Indonesia must elevate and consolidate its legal framework into a comprehensive Bill on Electronic Land Registration, which would serve as a solid foundation for building a holistic digital ecosystem of trust.